Search for invisible Higgs boson decays in vector boson fusion at √s=13 TeV with the ATLAS detector - Aaboud, Morad; Andrei, George Victor; Antel, Claire; Bolz, Arthur; Brandt, Oleg; Dunford, Monica; Ferreira de Lima, Danilo Enoque; Franchino, Silvia; Jongmanns, Jan; Kugel, Andreas; Napolitano, Fabrizio; S̜ahinsoy, Merve; et al. (Physics letters, 2019)
We report a search for Higgs bosons that are produced via vector boson fusion and subsequently decay into invisible particles. The experimental signat…
Im Titel steht der Buchstabe s unter dem Wurzelsymbol
The ATLAS Collaboration: M. Aaboud, V.Andrei, C. Antel, A.E. Bolz, O. Brandt, M. Dunford, D.E. Ferreira de Lima, S. Franchino, J. Jongmanns, A. Kugel, F. Napolitano, M. Sahinsoy, A. Schoening, H-C. Schultz-Coulon, D. Sosa, T.M. Spieker, R. Stamen, P. Starovoitov, S.M. Weber, M. Wessels, X. Yue [und weitere]
Gesehen am 23.07.2019